Development of a protocol on adaptive collaborative water governance for improved Santa Cruz watershed management in the Philippines - David, Myra E.; Rola, Agnes C.; Pulhin, Juan M. (2016)
The study aimed to address the problem on the absence of formal mechanisms to govern water resources at the local level by developing a protocol on adaptive collaborative water governance (ACWG) to produce better outcomes in watershed management using a case study approach. The ACWG protocol underwent conceptualization and design processes. The conceptualization process began with the online search using a single, mixed or combination of key terms, such as, “natural resource management,” “adaptive,” “governance,” and “collaboration,” which consequently resulted to the evaluation of four models proposed by institutions based on some criteria. A model was reviewed on the bases: a) that it can be used as a tool to explore and explain factors and forces underpinning the development of a local specific water governance platform; b) of available descriptive activities per phase that can serve as guide in the conduct of a participatory action research; and c) that can be applied in a natural resource management setting. The processes involved in designing the ACWG are: a) review of the model structure and the elements or variables of the four models; b) categorization into four phases of similar-in-nature elements having the same purposes; and c) definition of protocol according to purposes, procedure, and some guidelines or recommendations. The guidelines are results of the implementation of the ACWG protocol in the Santa Cruz Watershed, Philippines. Some recommendations are elaborated to stress the importance of specific protocol processes in addressing the issue of absence of formal mechanisms in water resource governance.
Keywords: Watershed management